2015
DOI: 10.1097/iae.0000000000000540
|View full text |Cite
|
Sign up to set email alerts
|

Association of Prevascular Vitreous Fissures and Cisterns With Vitreous Degeneration as Assessed by Swept Source Optical Coherence Tomography

Abstract: Swept source optical coherence tomography imaging can identify PVF and cisterns occurring in the context of age-related VD, and PVF appeared to be possible precursors of cisterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…We have previously hypothesized the presence of PVF and cisterns in vivo based on limited crosssectional OCT sampling. 23 We also postulated that the PVFs are precursors to cisterns, since the base of both structures appeared to overlie superficial retinal blood vessels, and there was a trend towards an increasing prevalence of cisterns with advancing age, while the prevalence of PVFs declined. 23 It has been suggested that the development of PVFs results from a lack of hyalocytes overlying the retinal blood vessels.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…We have previously hypothesized the presence of PVF and cisterns in vivo based on limited crosssectional OCT sampling. 23 We also postulated that the PVFs are precursors to cisterns, since the base of both structures appeared to overlie superficial retinal blood vessels, and there was a trend towards an increasing prevalence of cisterns with advancing age, while the prevalence of PVFs declined. 23 It has been suggested that the development of PVFs results from a lack of hyalocytes overlying the retinal blood vessels.…”
Section: Discussionmentioning
confidence: 94%
“…23 We also postulated that the PVFs are precursors to cisterns, since the base of both structures appeared to overlie superficial retinal blood vessels, and there was a trend towards an increasing prevalence of cisterns with advancing age, while the prevalence of PVFs declined. 23 It has been suggested that the development of PVFs results from a lack of hyalocytes overlying the retinal blood vessels. 5,23 Subsequent syneresis may then lead to the expansion of the PVFs, eventually forming cisternal spaces.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our current understanding of posterior vitreous anatomy has recently been augmented by swept-source optical coherence tomography (SS-OCT) which allows an enhanced depth of field [24]. Furthermore, manipulation of image capture using standard spectral-domain optical coherence tomography (SD-OCT) allows for improved visualization of structures within the posterior vitreous [5, 6].…”
Section: Methodsmentioning
confidence: 99%
“…Given the enlargement of the bursa in the 12-yearold, one may hypothesize that this either represents very early degeneration or may, in fact, be congenital or acquired in very early childhood. In support of early degeneration, perimacular cisterns noted in the cortical vitreous have recently been correlated with higher grades of vitreous degeneration by Pang and associates [6]. Examining younger affected individuals and following them longitudinally will help elucidate this question.…”
Section: Dear Editormentioning
confidence: 95%